2021
DOI: 10.1007/s00425-021-03708-y
|View full text |Cite
|
Sign up to set email alerts
|

Topically delivered 22 nt siRNAs enhance RNAi silencing of endogenous genes in two species

Abstract: Main conclusion 22 nt siRNAs applied to leaves induce production of transitive sRNAs for targeted genes and can enhance local silencing. Systemic silencing was only observed for a GFP transgene. Abstract RNA interference (RNAi) is a gene silencing mechanism important in regulating gene expression during plant development, response to the environment and defense. Better understanding of the molecular mechanisms of this pathway may lead to future str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…(1) All sprayed 22-nt siRNAs triggered transitivity towards both their 5ʹ and 3ʹ, demonstrating that siRNAmediated transitivity is bi-directional and not unidirectional in agreement with previous studies (Hendrix et al, 2021a;Vaistij et al, 2002). ( 2) Despite targeting different regions on the GFP transcript, the three applied 22-nt siR-NAs produced very similar transitivity patterns, suggesting that they were not used as primers for RDR6 (otherwise transitivity would have spread only towards the 5ʹ upstream region of each siRNA trigger), corroborating previous reports (Hendrix et al, 2021b;Moissiard et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…(1) All sprayed 22-nt siRNAs triggered transitivity towards both their 5ʹ and 3ʹ, demonstrating that siRNAmediated transitivity is bi-directional and not unidirectional in agreement with previous studies (Hendrix et al, 2021a;Vaistij et al, 2002). ( 2) Despite targeting different regions on the GFP transcript, the three applied 22-nt siR-NAs produced very similar transitivity patterns, suggesting that they were not used as primers for RDR6 (otherwise transitivity would have spread only towards the 5ʹ upstream region of each siRNA trigger), corroborating previous reports (Hendrix et al, 2021b;Moissiard et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Some reports have shown that topically applied dsRNA can move systemically across plant tissues to prevent pathogen colonization even in the unsprayed regions (Koch et al, 2016;Mitter et al, 2017;Song et al, 2018). Systemic silencing was also demonstrated (Hendrix et al, 2021), where it was hypothesized that 22-bp siRNAs could induce silencing in systemic regions of Nicotiana benthamiana by secondary siRNA generation. The key to a prolonged and robust silencing induced by sprayed dsRNA can be attributed to their systemic nature.…”
Section: Discussionmentioning
confidence: 99%
“…However, the examples documented in the literature are limited. What has emerged from these studies is that exogenous RNAs are more efficient at suppressing transgenes than endogenous ones 36,58,61,62,65 . It has been suggested that the high level of transgene transcription, which is quite often regulated by strong promoters, can cause aberrant transcripts that produce secondary dsRNAs 58 .…”
Section: Treatmentmentioning
confidence: 99%